Conjugate point Observation Syowa-Iceland - Natsuo SATO; Yutaka KATSUTA; Masaru AYUKAWA; Hiroshi FUKUNISHI; Takeo HIRAWASA (National Institute of Polar Research, 1979)
Conjugate observations of ELF-VLF emissions, geomagnetic pulsations and auroras were carried out at Syowa Station in Antarctica and at Husafell in Iceland from July 29, 1977 to September 18, 1977 Husafell is located at a distance of about 60 km from the conjugate point of Syowa From a prelimmary analysis of the ELF and VLF emission data, the following results were obtained 1) Conjugacy of auroral chorus emissions observed in the early morning is low. The emission intensity is larger at Husafell than at Syowa. 2) Daytime ELF chorus emissions show a good conjugacy. However, it is found that the intensity in the low frequency range is greater at Syowa than at Husafell, and vice versa in the high frequency range. 3) QP emissions are observed simultaneously at the conjugate-pair stations. 4) Conjugacy of auroral hiss emissions is generally low during this observation period. The intensity is much higher at Syowa (winter hemisphere) than at Husafell (summer hemisphere)